Validation of Accelerometer Cut-Points in Children With Cerebral Palsy Aged 4 to 5 Years. Issue 4 (2016) - Keawutan, Piyapa; Bell, Kristie L.; Oftedal, Stina; Davies, Peter S. W.; Boyd, Roslyn N.
Abstract : Purpose: To derive and validate triaxial accelerometer cut-points in children with cerebral palsy (CP) and compare these with previously established cut-points in children with typical development. Methods: Eighty-four children with CP aged 4 to 5 years wore the ActiGraph during a play-based gross motor function measure assessment that was video-taped for direct observation. Receiver operating characteristic and Bland-Altman plots were used for analyses. Results: The ActiGraph had good classification accuracy in Gross Motor Function Classification System (GMFCS) levels III and V and fair classification accuracy in GMFCS levels I, II, and IV. These results support the use of the previously established cut-points for sedentary time of 820 counts per minute in children with CP aged 4 to 5 years across all functional abilities. Conclusions: The cut-point provides an objective measure of sedentary and active time in children with CP. The cut-point is applicable to group data but not for individual children. Abstract : Supplemental Digital Content is Available in the Text.Accelerometers are investigated as an objective measure of sedentary and active time in children with CP.